Antioxidant, Enzyme Inhibitory and Calcium Oxalate Anti-crystallization_x000D_ Activities of Equisetum telmateia Ehrn. - (:unkn) unknown (My University, 2020)
Equisetum L. is the only genus of the Equisetaceae family, whichcommonly known as horsetails, in English and atkuyruğu or kırkkilit inTurkish. In traditional medicine, Equisetum telmateia Ehrh. is used in diseasesof the urinary system, such as pyelonephritis, prostatic hypertrophy, andcystitis. Besides, this species is known to be used by humans to treat kidneystones or kidney sand. The extracts were obtained from the aerial parts of theE. telmateia using three different extraction methods (maceration, Soxhlet,ultrasonic bath) and their antioxidant (ABTS, CUPRAC), anti-urease andanticholinesterase activities were examined. Also, calcium oxalate anticrystallizationactivity of Soxhlet methanol extract showing strong antioxidantactivity was determined. Soxhlet methanol extract exhibited stronger ABTSradical scavenging (0.0676 mM Trolox/mg extract) and cupric ionreducing/antioxidant (4.351 mM Trolox/mg extract) activity than otherextracts. Soxhlet methanol (65.528%) and maceration methanol (61.965%)extracts showed the strongest anticholinesterase activity. In the anti-ureaseassay, it was found that Soxhlet petroleum ether extract (15.302%) had thehighest anti-urease activity. Furthermore, the data obtained showed that theSoxhlet methanol extract had high efficacy in the nucleation and aggregationphase of calcium oxalate crystals. These results prove that Soxhlet methanolextract has antioxidant, anticholinesterase and anti-crystallization capabilities.Therefore, this extract can be used in the future as an antioxidant andanticholinesterase agent as well as the treatment and / or prevention of stoneformation.